Ultimate Performance of Anode-supported SOFC by Realizing Thin-film Electrolyte and Nano-structure Electrode - Noh, Ho-Sung; Yoon, Kyung Joong; Kim, Byung-Kook; Je, Hae-June; Lee, Hae-Weon; Lee, Jong-Ho; Son, Ji-Won (ELECTROCHEMICAL SOC INC, 2013)
The ultimate performance level of the solid oxide fuel cell (SOFC) at low operating temperatures by using thin-film electrolytes and nano-structure electrodes is discussed. By minimizing the external losses during the cell test, it is possible to precisely assess the impact of the thin-film electrolyte and the nano-structure electrodes which are realized on the anode supports, a realistic SOFC platform (anode-supported thin-film (TF)-SOFC). A peak power density reaching 600 mWcm(-2) at 500 degrees C is obtained, which we believe is nearing the highest level that the SOFC can reach while using the common SOFC materials and platforms, by changing the dimension of the cell components. The potential and limitations of anode-supported TF-SOFCs in achieving the critical low-temperature performance will be discussed.